2013
DOI: 10.1155/2013/610648
|View full text |Cite
|
Sign up to set email alerts
|

Potential Toxic Levels of Cyanide in Almonds (Prunus amygdalus), Apricot Kernels (Prunus armeniaca), and Almond Syrup

Abstract: Under normal environmental conditions, many plants synthesize cyanogenic glycosides, which are able to release hydrogen cyanide upon hydrolysis. Each year, there are frequent livestock and occasional human victims of cyanogenic plants consumption. The present work aims to determine the hydrocyanic acid content in different samples of cyanogenic plants, selected from the Tunisian flora, and in the almond syrup. In order to evaluate their toxicity and their impact on the consumer health in the short term as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 15 publications
0
36
0
1
Order By: Relevance
“…As a result, a small amount of Cbl in the blood stream is present in the Cn-Cbl form that binds cyanide residues. Cyanide is normally present in trace amounts in foods such as cassava, bitter almonds and apricot kernels (responsible for the bitter taste) [44]. H-Cbl is a form of cobalamin highly represented as a physiological intermediate [35].…”
Section: Chemical Properties Of Cobalamin and Vitamin Activitymentioning
confidence: 99%
“…As a result, a small amount of Cbl in the blood stream is present in the Cn-Cbl form that binds cyanide residues. Cyanide is normally present in trace amounts in foods such as cassava, bitter almonds and apricot kernels (responsible for the bitter taste) [44]. H-Cbl is a form of cobalamin highly represented as a physiological intermediate [35].…”
Section: Chemical Properties Of Cobalamin and Vitamin Activitymentioning
confidence: 99%
“…All these seeds contain the CNGs amygdalin and prunasin. While the level of cyanogens is rather low in the sweet variety of almonds (about 25 mg CN/kg), bitter almonds and apricots contain cyanogens at levels ranging from about 500 to more than 1,000 mg cyanide/kg (Chaouali et al., ). Marzipan is exclusively produced from the kernels of sweet almonds which do not need detoxification due to their low cyanogen content, which is further decreased by the manufacturing process (blanching, chopping and grinding with sugar into almond flour).…”
Section: Assessmentmentioning
confidence: 99%
“…Other authors refer that significant differences in the content of amygdalin, and consequently of HCN, in apricot kernels are due to geographical and climate characteristics. Chaouali et al (2013) noted that a dry climate and intense sunlight promote cyanogenesis, and that differences in amygdalin concentration may be also ascribable to different agricultural practices. Finally, it has been reported that the content of amygdalin may also vary according to the age of the plant at harvest time: amygdalin gradually increases during plant growth, reaching the highest concentrations at maturity (Chaouali et al, 2013).…”
Section: Previously Reported Occurrence Datamentioning
confidence: 99%